Power electronics for next-generation drives and energy systems. Volume 1, - Kumar, Nayan; Guerrero, Josep; Kastha, Debaprasad; Saha, Tapas Kumar (IET energy engineering series ;, 2022)
Power electronics converters are devices that change parameters of electric power, such as voltage and frequency, as well as between AC and DC. They are essential parts of both advanced drives, for machines and vehicles, and energy systems to meet required flexibility and efficiency criteria. In energy systems both stationary and mobile, control and converters help ensure reliability and quality of electric power supplies. This reference in two volumes is useful reading for scientists and researchers working with power electronics, drives and energy systems; manufacturers developing power electronics for advanced applications; professionals working in the utilities sector; and for advanced students of subjects related to power electronics. Volume 1 covers converters and control for drives, while Volume 2 addresses clean generation and power grids. The chapters enable the reader to directly apply the knowledge gained to their research and designs. Topics include reliability, WBG power semiconductor devices, converter topology and their fast response, matrix and multilevel converters, nonlinear dynamics, AI and machine learning. Robust modern control is covered as well. A coherent chapter structure and step-by-step explanation provide the reader with the understanding to pursue their research.